Fluoride concentrations in salt marketed in Managua, Nicaragua - Karla Irina Walsh; Jaime Aparecido Cury (Sociedade Brasileira de Pesquisa Odontológica, 2018)
Abstract Nicaraguan legislation has established that fluoride concentrations in salt should be 200-225 mg/kg, but no report describes fluoride concentrations in salt marketed in this country. We evaluated the fluoride concentrations in 33 packages of salt of 11 brands (n = 3 each) purchased in Managua, Nicaragua. According to the package information, 9 of the 11 brands were fluoridated. Six aliquots of each package were weighed (mean 2.5 ± 0.3 g; n = 198) and dissolved in 0.025 g/ml water. Duplicates of 1.0 ml of solutions prepared were buffered (1:1; v/v) with TISAB II. Fluoride concentrations were determined with ion-specific electrode, calibrated with standard solutions (0.25-16.0 μg F/ml) mixed (1:1; v/v) with TISAB II added to 0.025 g (p.a.) NaCl/ml. The mean (± standard deviation, n = 3) fluoride concentrations of two fluoridated brands were in accord with Nicaraguan law (209.8 ± 48.0 and 211.4 ± 26.0 mg F/kg), and those of five brands were below the mandated range (131.0 ± 34.3, 180.6 ± 12.3, 184.6 ± 34.8, 190 ± 47.2, and 199.0 ± 18.9 mg F/kg); two brands contained only traces of fluoride. The two non-fluoridated brands had traces of fluoride. The findings show that the surveillance system for the salt fluoridation program in Nicaragua should be improved, as most salt analyzed violated the requirements of the national legislation.